2018
DOI: 10.1002/pop4.211
|View full text |Cite
|
Sign up to set email alerts
|

Quantification and Scientism in Political Science: Domination of Discourse by Experts Presenting Mathematical Models of Reality

Abstract: Mathematization has become increasingly dominant in the social sciences. Political science research reflects this trend. Unfortunately, complex mathematical models do not reflect reality and have little relevance to public political discourse. Indeed, much of the quantification in political science research is fraught with fallacies, not the least of which are reification and scientism. Even simple statistical models such as crosstabs and simple tests such as Pearson's‐chi square are fallacious but not well un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
1
0
1
Order By: Relevance
“…Por otro lado, el abordaje cuantitativo suele ser considerado una de las fuentes (sino la fuente) de los principales desvíos, distorsiones y limitaciones que son atribuidos a la disciplina (Donovan y Larkin, 2006). Las ansias de medición habrían exacerbado el tecnicismo, el formalismo y la especialización fragmentadora, perdiendo de vista al propio fenómeno político (Kingsley, 2018). Es extendida la apreciación de que "la ciencia política dominante ha adoptado un modelo inapropiado de ciencia política" siendo una de sus principales características ser "tan cuantitativa y estadística como fuera posible" (Sartori, 2004, p. 351).…”
Section: El Abordaje Cuantitativo En La Ciencia Política Y El Caso La...unclassified
“…Por otro lado, el abordaje cuantitativo suele ser considerado una de las fuentes (sino la fuente) de los principales desvíos, distorsiones y limitaciones que son atribuidos a la disciplina (Donovan y Larkin, 2006). Las ansias de medición habrían exacerbado el tecnicismo, el formalismo y la especialización fragmentadora, perdiendo de vista al propio fenómeno político (Kingsley, 2018). Es extendida la apreciación de que "la ciencia política dominante ha adoptado un modelo inapropiado de ciencia política" siendo una de sus principales características ser "tan cuantitativa y estadística como fuera posible" (Sartori, 2004, p. 351).…”
Section: El Abordaje Cuantitativo En La Ciencia Política Y El Caso La...unclassified
“…For a number of years, the ACA was unpopular among the majority of Americans, largely due to conservative propaganda. 47 Although the ACA has been much-maligned primarily for political purposes, research demonstrates that it reduces out-of-pocket expenses for health care dramaticallyparticularly for lower-income individuals. 48 Consequent to this research coupled with a divisive lack of trust for the current administration, 49 a recent Kaiser Family Foundation poll predictably indicated that a clear majority of Americans are now in favor of the ACA.…”
mentioning
confidence: 99%